Aerodynamic Performance and Noise Characteristics of Modified Blade Tip of Small HAWT - Iswahyudi, Sigit; Wibowo, Setyawan Bekti; Suyitno, Suyitno; Suprihanto, Agus (Journal of Engineering and Technological Sciences, 2024)
The planform design of a wind turbine blade influences its aerodynamic performance and noise characteristics, with the tip shape controlling vortex shedding, power, and noise. This study examined the tip shape’s effect on a small horizontal-axis wind turbine (HAWT). Field tests were conducted on three rotors: one with straight blades, one with low swept angle (12° and 61° sweep, 15° anhedral) blades, and one with high swept angle (32° and 72° sweep, 15° anhedral) blades. All had three blades, a tip speed ratio (TSR) of 5.24, and an NACA 4412 cross-section. The basic blade rotor and the modified blade 1 rotor had a 2.1 m diameter, while the modified blade 2 rotor had a 2.8 m diameter. The modified blades had revised tips along 10% of the radius. The results showed maximum power coefficients of 0.25, 0.2, and 0.15 for the basic blade, modified blade 1, and modified blade 2, respectively. modified blade 2 exhibited the best starting behavior, needing only 1 m/s wind speed. It also reduced low-frequency noise while increasing high-frequency noise, which is more effectively absorbed by the atmosphere. The swept blade tips lowered power performance but improved start-up and reduced low-frequency noise